Extraction of natural dyes from tarum leaves (Indigofera Tinctoria L.) using the Ultrasound-Assisted Extraction (UAE) method - Yeni Variyana; Livia Rhea Alvita; Najlaa Ariibah Meutia; Aphrodita Luthfania Eka Putri; M. Mahfud (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
The rapid development of the textile industry has led to increased use of synthetic dyes. Although synthetic dyes are more practical and economical, their use can have adverse effects on health and the environment. Natural dyes are utilized as alternatives with indigo leaves (Indigofera tinctoria L.) being one source known for producing a blue color. However, the commonly used extraction methods require long extraction times and significant solvent consumption. Given the limitations of current methods, innovation is needed for an efficient extraction method that produces safe and environmentally friendly natural dyes, one of which is ultrasound-assisted extraction (UAE). Therefore, this study aims to determine the extraction process of indigo leaves using UAE method, then identify the parameters influencing the extraction process using the UAE, determine the extraction yield using UAE, assess the dyeing results of the extracted dye from indigo leaves on cotton fabric, and compare the extraction results of indigo dye through the UAE method with the addition of CaO and NaOH solutions. The results of this study indicate that the natural dye from Indigofera tinctoria obtained the best conditions at extraction time of 90 min, feed-to-solvent ratio of 0.05 g/ml, and CaO-to-solvent ratio of 0.005 g/ml. Furthermore, the addition of CaO solution obtained the highest yield at 4.25 %, while the addition of NaOH solution resulted in 4.8 %. Additionally, the analysis and test results of the application of natural dye from Indigofera tinctoria on cotton fabric revealed a darker color with the addition of NaOH solution compared to the addition of CaO solution.